1992
DOI: 10.3758/bf03206714
|View full text |Cite
|
Sign up to set email alerts
|

Differential thresholds for limb movement measured using adaptive techniques

Abstract: Differential thresholds for limb movement were measured in 10 subjects, using the transformed up-down procedure. Subjects were required to indicate which of two random displacement perturbations delivered to their forearms had the larger standard deviation (Sm. The SD of the reference signal was fixed for each experimental condition at one of seven values ranging from 0.05 to 3.2 mm. The SD of the other signal varied depending on the subject's response. Using this procedure, the differential threshold for limb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
(30 reference statements)
0
19
0
Order By: Relevance
“…The reported WF for stiffness is about 23% [15], [16] and that for inertia is about 21% [11]. These WFs are relatively larger than the reported WFs for force and displacements, which are in the 6%-8% range [12], [13], [29], [30]. Since humans possess no inertia-specific or stiffness-specific "sensors" in the peripheral sensory organs, the reported data is evidence of a loss of sensory resolution when force and displacement cues are combined.…”
Section: Discussionmentioning
confidence: 96%
“…The reported WF for stiffness is about 23% [15], [16] and that for inertia is about 21% [11]. These WFs are relatively larger than the reported WFs for force and displacements, which are in the 6%-8% range [12], [13], [29], [30]. Since humans possess no inertia-specific or stiffness-specific "sensors" in the peripheral sensory organs, the reported data is evidence of a loss of sensory resolution when force and displacement cues are combined.…”
Section: Discussionmentioning
confidence: 96%
“…Early kinesthetic studies by Clark and colleague and Jones and Hunter (Clark & Horch, 1986;Clark, 1992;Jones & Hunter, 1992) investigated human perception of limb positions and concluded that humans are capable of detecting joint rotations of a fraction of a degree performed over a second of time interval. Jones and Hunter (1992) also reported the differential threshold for limb movement as 8 percent.…”
Section: Human Haptic Perceptionmentioning
confidence: 99%
“…o down method was used to calculate thresholds (see, e.g., Jones et al, 1992). As it was implemented, the latter procedure sought a stimulus level that corresponded to 71% correct performance.…”
Section: 2 3mentioning
confidence: 99%
“…The subjects were required to indicate which ofthe two low-pass filtered (with a cutoffat 15 Hz) signals had the larger amplitude (defined in terms of the root-mean square [RMS] deviation). It was found that subjects could reliably discriminate an 8% difference in the RMS deviation amplitude of two random displacements and, at the smallest amplitude, were able to resolve a 5-J.lm difference between the two perturbations (Jones et al, 1992). The latter accomplishment probably reflects the perception of skin indentation and not movement of the forearm.…”
mentioning
confidence: 93%
See 1 more Smart Citation